Testing the Antibacterial Activity of Black Betel Leaf Extract (Piper betle L. Var Nigra) on Streptococcus mutans, Porphyromonas gingivalis, and Enterococcus faecalis - Cici Nur Aisyah Eka Putri; Masyhudi Masyhudi; Listiyawati Listiyawati (Jurnal Impresi Indonesia, 2024)
Black betel leaves (Piper betle L. var nigra) are known to have antibacterial effects caused by secondary metabolites such as tannins, phenolic compounds, saponins, flavonoids, alkaloids, and steroids. This study aims to assess the antibacterial activity of ethanol extract of black betel leaves (Piper betle L. var nigra) against S. mutans, P. gingivalis, and E. faecalis by measuring the diameter of the inhibition zone formed. This research is a type of pure experimental research (true experimental) with post test only control group design. This experimental research was conducted using the disc diffusion method in vitro, the bacteria were treated with black betel leaf extract (Piper betle L. var nigra) with a concentration variation of 60%, 70%, 80%, 90%, and 100%. The experiment was repeated three times. The results showed that black betel leaf (Piper betle L. var nigra) had antibacterial activity against two of the three bacteria. This activity was observed through the presence of distinct clear zones around the paper disks. In conclusion, extracts derived from black betel leaf (Piper betle L. var nigra) had antibacterial activity against S. mutans and P. gingivalis bacteria at 70%, 80%, 90%, and 100% concentrations. However, it did not have antibacterial activity against E. faecalis bacteria.